Utilization Of Social Media For Prmotion Of Small And Medium Busisesses In Intestine Chips In Seginim Village - Cantika, Yella; Abi , Yudi Irawan; Anggriani , Ida (Multidisciplinary Journals, 2024)
This study aims to analyze the use of social media for promotional for small and medium SMEs on intestine chips products in seginim village. In the current digital era,social media has become a very effective tool for increasing product visibility and marketing. This study uses qualitave descriptive metdhods with tecniques data collection through in depth intervews, observation and document analysis, the result of this research show that usesrs of social media platformsuch as fecebook, instagram, and whatsapp have had a positive impact on increasing sales and (brend awareness) of intestinal chips product. SMEs in seginim villages use social media for various promotional activities. Inluding product introductions, providing information to consumers,apart from to consumers,apart from that,interesting and interactive content strategies such as product images and vides, costumer reviews and special offers have proven to be effective in attracting consumer attention and interest.